Revealing the relation between microstructural heterogeneities and local mechanical properties of complex-phase steel by correlative electron microscopy and nanoindentation characterization. (May 2021) - Chang, Yuling; Lin, Mingxuan; Hangen, Ude; Richter, Silvia; Haase, Christian; Bleck, Wolfgang
Abstract: Compositional and microstructural heterogeneity are characteristics of modern multiphase steels. However, the quantitative characterization of these heterogeneities is rarely considered in scientific publications. We characterized the compositional and microstructural heterogeneity of a commercial complex-phase steel (CP800) by combining various electron microscopy techniques and nanoindentation. Compositional gradients of C and Mn were characterized qualitatively and quantitatively through electron probe microanalysis (EPMA). Electron backscatter diffraction (EBSD) results were utilized to identify and segment the microstructural constituents. A novel nanoindentation approach was used to obtain hardness maps. Cube-corner indenter and micro-newton load were applied to limit the indent depth and spacing between adjacent indents to the nanometer scale. A high-resolution hardness map was obtained and successfully overlapped with EPMA and EBSD results, based on which the correlation between compositional heterogeneity and hardness variation in complex-phase microstructure was successfully established. Graphical abstract: Unlabelled Image Highlights: By applying a novel nanoindentation technique, a hardness map with nanometer-scale resolution was obtained. Correlative characterization method combining various electron microscopic techniques and nanoindentation was developed. Results indicated the unneglected influence of Mn bands on local microstructure and hardness in the complex-phase steel. Martensite introduced the severest hardness change regardless of the neighboring phases in the complex-phase steel.